Driving Sustainability: Analyzing the Influence of Road Transportation Infrastructure on Green Economic Growth in Malaysia - Zulkefli, Nurul Aini Izzati; Muda, Ruhaini; Mokhtar, Imani; Viverita, V. (Advances in Social Sciences Research Journal, 2024)
Road infrastructure is an important aspect of the green economy. It integrates environmental, social, and economic factors with the aim of generating a positive net environmental balance. The green Solow growth model proposes that road infrastructure can enhance economic growth while improving environmental quality. This paper examines the relationship between transportation infrastructure and green economic growth in Malaysia, with the aim of ascertaining whether road transportation infrastructure has a role in sustaining economic growth. The study makes use of time series data over the period 1970-2021. This study employs the autoregressive distributed lag (ARDL) model and the error correction model (ECM). The study analyses three models of the total road network and segregates them into federal roads and state roads. The findings show that there are negative long-run relationships between transportation infrastructure and green economic growth. The results also showed that Federal Road had a more negative impact on green economic growth. However, in the short run, only Federal Road shows a significant and negative impact on green economic growth. In Malaysia, the federal road is classified as a primary road extensively utilised by the populace for their routine activities. Thus, federal roads have the potential to generate a more immediate and substantial influence on sustained economic development in comparison to state roads. Nevertheless, road transportation infrastructure can also have adverse effects on the sustainability of long-term economic growth. This study sheds light on the importance of sustainable road development that balances economic growth and the preservation of the environment.